2016
DOI: 10.1177/1049909115625960
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ultrasound in Palliative Care and Hospice

Abstract: Palliative care aims to reduce symptom burden and enhance quality of life for those with terminal disease. Ultrasound has become an increasingly popular diagnostic and therapeutic modality due to its low cost, ease of portability, safety, and good patient acceptance. A review of the literature to date shows that as a diagnostic tool, as a therapeutic modality, and as a tool to accurately guide palliative procedures, ultrasound can have many roles in palliative care and hospice. Based on our clinical experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
(69 reference statements)
0
12
0
2
Order By: Relevance
“…The rehabilitation intervention group also utilized fewer resources [ 53 ••]. Furthermore, studies have shown that musculoskeletal pain is prevalent at the end of life [ 54 ], and the rise of ultrasound-guided procedures is allowing more rapid intervention for acute pain during hospice, opening avenues for physiatric management of end-of-life pain [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rehabilitation intervention group also utilized fewer resources [ 53 ••]. Furthermore, studies have shown that musculoskeletal pain is prevalent at the end of life [ 54 ], and the rise of ultrasound-guided procedures is allowing more rapid intervention for acute pain during hospice, opening avenues for physiatric management of end-of-life pain [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…A small but growing literature discusses the use of ultrasound and paracentesis in community-based palliative care settings, mostly at the bedside. 18 -21 Our article adds an important dimension to this body of research by demonstrating the feasibility and benefits of this procedure in an outpatient setting, particularly in the vulnerable period after hospital discharge.…”
Section: Discussionmentioning
confidence: 94%
“…Kas iskelet sistemi problemleri palyatif bakım popülasyonunda önemli bir ağrı nedenidir. Ultrason, terminal dönem hastaların yaşam kalitesinin artırılmasında rol oynayabilir ancak, ağrının giderilmesinde ultrasonu destekleyen çok az kanıt vardır (31).…”
Section: Ultrasonunclassified